2017
DOI: 10.1155/2017/9810978
|View full text |Cite
|
Sign up to set email alerts
|

The Dispersion Rule of Fragments about the Asymmetric Shell

Abstract: In order to obtain the dispersion rule of fragments about the asymmetric shell subjected to internal blast loading, two different cross section structures, concave-shaped and convex-shaped, were carried out by experimental and numerical methods. The simulation results well coincided with the experimental results, and the spatial distribution and fragment velocity were obtained. The optimal curvatures for the different concave structures changed from 4r to 6r (r represents the charge radius), as the central ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 11 publications
2
14
0
Order By: Relevance
“…The mechanical parameters of the material model were not the default parameters in LS-DYNA, which were provided by the material supplier. These material parameters had been verified by numerical simulations and experiments, the detailed analysis of which can be found in Ding et al 28 …”
Section: Fe Modelmentioning
confidence: 81%
See 1 more Smart Citation
“…The mechanical parameters of the material model were not the default parameters in LS-DYNA, which were provided by the material supplier. These material parameters had been verified by numerical simulations and experiments, the detailed analysis of which can be found in Ding et al 28 …”
Section: Fe Modelmentioning
confidence: 81%
“…Gong et al 26 and Wang et al 27 reported an empirical formula and a new method to estimate the projection angles and fragment velocities of D-shaped cylindrical casing. Ding et al 28 studied the spatial distribution and velocity of fragments about the concave-shaped and convex-shaped asymmetric structures.…”
Section: Introductionmentioning
confidence: 99%
“…After detonating the explosive charge in the casing, the shell is broken into fragments that have equal velocity in all radial directions. However, in the recent research of aimable warhead, sometimes the explosive charge is not detonated on the axis, and even the casing itself may not necessarily be axially symmetric at all [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of asymmetric casing, the explosive loading on the shell is not equal at different azimuth angles, and the circumferential velocity distribution is thus not uniform. Besides, the fragments may converge or disperse after detonation [2]. For designing novel warheads, it is therefore essential to study the fragment velocity distribution of asymmetric casings under internal explosive loading.…”
Section: Introductionmentioning
confidence: 99%
“…The asymmetric cylindrical structure can be roughly divided into three types: the concave-shaped, convex-shaped, and D-shaped. The research on concave-shaped and convex-shaped types has been described in another article [20]. Therefore, this paper mainly focuses on the D-shaped structure, and several experiments were carried out to investigate the influence of the central angle on the spatial distribution, fragment velocity and energy output.…”
Section: Introductionmentioning
confidence: 99%